PENOLAKAN PENERBITAN KEPUTUSAN OLEH LURAH KEPUTIH BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANGADMINISTRASI PEMERINTAHAN (STUDI PUTUSAN PTUN SURABAYA NO.19/P/FP/2019/PTUN.SBY.): The Refusal to Issue a Decision by The Head of Keputih Village Based on Law Number 30 of 2014 Concerning Government Administration (Case Study of The Surabaya Administrative Court Decision NO.19/P/FP/2019/PTUN.SBY.) - Axel Matthew Lambert Setyoadi; Yogo Pamungkas (AMICUS CURIAE, 2025)
This study reviews the refusal to issue a decision by the Lurah Keputih based on Law Number 30 of 2014 concerning Government Administration (Case Study of Surabaya Administrative Court Decision No. 19/P/FP/2019/PTUN.SBY). The main issue discussed in this study is whether the actions of Lurah Keputih in not issuing the requested certificate contradict Law No. 30 concerning Government Administration. To answer this issue, the research employs a juridical-normative method with a descriptive nature, using secondary data as the primary data processed qualitatively. Conclusions are drawn using deductive logic. This study concludes that the actions of the Government Official in not issuing the requested certificate without a reason that meets the requirements are contrary to Law No. 30 concerning Government Administration. The legal consequence of this act is that it constitutes a positive fictitious action due to the neglect in issuing a decision, and the concerned Government Official is subject to administrative sanctions such as paying court costs and issuing what was requested by the Applicant.